Retrospective Total cost of ownership analysis of battery electric vehicles in Norway. (April 2022) - Figenbaum, Erik
Highlights: Purchase incentives and local incentives made battery electric vehicles competitive. Total cost of ownership was from 2012 lower than for 3-year old gasoline vehicles. Battery electric vehicles became from 2012 economic to own for multivehicle owners. Sales increased with model availability from 2012 as incentives were kept in place. Abstract: A retrospective Total Cost of Ownership (TCO) analysis of battery electric vehicles (BEVs) versus gasoline vehicles (ICEVs), provided insights on the TCO effects of Norway's BEV incentives that counts the registration and value added tax exemptions, reductions/exemptions from the annual tax, parking fees, road tolls and ferry rates, and bus lane access. BEVs were according to the TCO calculation too expensive before 2001. A 2001 breakthrough failed when California revised the ZEV-mandate and the Norwegian BEV producer THINK owned by Ford had problems. The TCO has since 2012 been favorable also compared to 3-year old ICEVs. The latter enabled adoption in multi-vehicle households that effortlessly coped with BEVs limited range, through the access to another vehicle for long trips and vacations. BEVs got a good reputation. Adoption targets were revised upwards when old targets were met. The costly incentives became institutionalized and difficult to downscale without hurting the successful market.